Smart Nanosystems for Biomedicine, Optoelectronics and Catalysis - Shabatina, Tatyana; Bochenkov, Vladimir (IntechOpen, 2020)
Nowadays nanoscience and nanotechnologies provide us with many excellent examples of the unique solutions for the different technical problems and demands of human society. Smart stimuli-responsive nanosystems and nanomaterials are used in many fields such as medicine, biomedical, biotechnology, agriculture, environmental pollution control, cosmetics, optics, health, food, energy, textiles, automotive, communication technologies, agriculture, and electronics. The book "Smart Nanosystems for Biomedicine, Optoelectronics and Catalysis" describes the modern trends in nanoscience and nanotechnology for creation of smart hybrid nanosystems combining the inorganic nano-objects with organic, biological, and biocompatible materials, which create multifunctional and remotely controlled platforms for diverse technical and biomedical uses. The material includes several review and original research articles devoted to the problems of directed chemical and biological synthesis of such nanosystems, thorough analysis of their physical and chemical properties and prospects of their possible applications. We hope that the presented book will be useful for different nanoscience research groups and PhD and graduate students, to introduce them to the world of hybrid metal-organic and metal-biological nano-objects, and smart self-organizing nanosystems and open new ways of their possible use in different scientific and practical areas.